Rejection against the Patriarchal Society in Stephen Chbosky and Evan Spiliotopoulos Beauty and The Beast - Marssy Diana Sampe (Universitas Sanata Dharma, 2022)
Liberal feminism is a movement that focuses on individual freedom. This idea reflects women's liberation: women should have the same rights and opportunities as men in education, economy, politics, rights, and other gender inequality issues. The research aims to analyse Beauty and the Beast film's script through liberal feminism's lenses. This research uses a library research method that applied feminist criticism. Reading and selecting data techniques were used to collect the data. The film script of Beauty and the Beast used the data. To analyse the patriarchal society in the script, theories by Hooks and Beauvoir were used. The analysis results show that men have control and power to dominate people, especially women, and women do not enjoy the dignity of being a person; they do not have anything unless they are part of men's patrimony. To analyse the rejection done by Belle, theory by Freedman was used. The result shows that Belle rejects the social convention by reflecting the value of liberal feminism and individual autonomy. The implication in the story that insists on the voice of equality between gender, women deserve the right to get a proper education, liberty, justice, and the same rights as men.